A Method of Synchronization Switching between Frequency Converter and Grid - 张少云; 刘斐; 张铁军; 陈刚 (Kongzhi Yu Xinxi Jishu)
Bypass mode is one of the important running modes of frequency converters. It may incur current surge and serious electromagnetic interference (EMI) if the switching method between frequency converter and grid is incorrect. It presents a calculation method of power frequency with software, and introduces a way to improve switching performance using phase lock loop which make the output frequency and phase angle of inverter are the same.